EFEKTIVITAS PROGRAM BANTUAN RUMAH TIDAK LAYAK HUNI DI KECAMATAN PONTIANAK KOTA - Widya Yulianti E.42009082 (FISIP Universitas Tanjungpura Pontianak, 2022)
The purpose of this study is to describe and analyze the effectivity of Unlivable house in Pontianak City subdistrict. The title of this study was appointed by the problems, about the implementation of the unlivable house program still many irregularities. Where to find out whether or not the effectivity of the program it is necessary to measure effectiveness through the existing problems in the implementation. This research use descriptive study with qualitative approach. Data collection techniques are observation, interview and documentation. The study subjects were clerks Department of Human Settlements, Housing and Spatial Pontianak, head of Pontianak City subdistrict, Head of Community Development, PNPM members, and residents who receive assistance Unlivable Homes Program. The conclusion of this study is, unlivable house program very effective and really help the economy of the people, for knowing the effective or not of that program is an effective indicator of the clarity of strategy, programming, and system monitoring and control, while the indicator are not effective that the goal has not been achieved and plans that are less mature. It is necessary for the socialization of the government to make the program even better. Keywords: Effectiveness, Program, Planning, Monitoring, Implementation.